Leptospirosis among Dengue-Negative Febrile Patients in Selangor, Malaysia - Loong, Shih Keng; Abd-Majid, Mohamad Azlan; Teoh, Boon Teong; Cheh, Mi Jing; Khor, Chee Sieng; Chao, Chien Chung; Khoo, Jing Jing; AbuBakar, Sazaly (The American journal of tropical medicine and hygiene, 2022)
In recent years, the number of leptospirosis cases, including the number of deaths, has exponentially increased in Malaysia. From June 2016 to February 2018, blood samples of 321 febrile patients with the presumptive diagnosis of dengue-like illness were examined for possible exposure to Leptospira . Two hundred fifty-five blood samples were tested as negative for dengue. Seminested polymerase chain reaction (PCR) and IgM ELISA for leptospirosis were performed. From the samples, an overall prevalence for leptospirosis based on PCR of 4.7% (12/255) was obtained. Eighteen percent (46/255) were positive for anti- Leptospira IgM antibodies. The genome sequences of six of 12 Leptospira PCR-positive samples showed > 97.0% similarity to Leptospira interrogans . One patient’s sample consisted of Leptospira and chikungunya virus, suggesting a coinfection. Findings from the study suggest that leptospirosis is prevalent among dengue-negative febrile patients in Malaysia.